2018
DOI: 10.1051/ocl/2018048
|View full text |Cite
|
Sign up to set email alerts
|

Tamanu oil and skin active properties: from traditional to modern cosmetic uses

Abstract: Calophyllum inophyllum L. (Calophyllaceae), locally called “tamanu” in French Polynesia, is an evergreen pantropical tree growing mostly along the seashores. Its barks, leaves, and fruits are still used in traditional medicine. The oil expressed from the nuts has been also traditionally used. Tamanu oil is topically applied on skins as well as mucous membrane lesions. This oil is especially recommended to heal all kinds of skin ailments. Bioassays and different assessments of Tamanu oil revealed numerous biolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 14 publications
0
32
0
2
Order By: Relevance
“…The above summary clearly shows that the incorporation of rarely studied tamanu and black cumin oils in emulsions can be of benefit, as they contain active ingredients with biological and pharmaceutical effects (treatment of asthma, bronchitis, skin diseases; antimicrobial, anti-inflammatory effects; and, gastro-protective properties) [8,9,26,27]. Moreover, the stabilizing of emulsions containing these oils with biocompatible and biodegradable protein CAS can facilitate the delivery of oils to hydrophilic systems while also protecting them against degradation.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…The above summary clearly shows that the incorporation of rarely studied tamanu and black cumin oils in emulsions can be of benefit, as they contain active ingredients with biological and pharmaceutical effects (treatment of asthma, bronchitis, skin diseases; antimicrobial, anti-inflammatory effects; and, gastro-protective properties) [8,9,26,27]. Moreover, the stabilizing of emulsions containing these oils with biocompatible and biodegradable protein CAS can facilitate the delivery of oils to hydrophilic systems while also protecting them against degradation.…”
Section: Introductionmentioning
confidence: 93%
“…This difference was again wiped off in emulsions that were prepared using US. The fact that TA oil also contains, in addition to neutral lipids and glycolipids, phospholipids (1.6%), small amounts of sterols, and mono-and diacylglycerols, which all have emulsifying properties, can also contribute to easier formation of smaller droplets [9].…”
Section: Droplet Size and Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Atabani et al [35] determined the refractive index of C. inophyllum oil as 1.478. Phila Raharivelomanana et al [36] reported the refractive index of C.inophyllum oil was found to be 1 .474. and -4.07 o C respectively, but clonal variation in these properties were insignificant. The flash point is the temperature at which fuel vapor given off momentary flash when an external flame is introduced under specified test conditions.…”
Section: Resultsmentioning
confidence: 99%
“…In this dossier, you will find some of the topics covered throughout this congress through the following articles of the speakers: relations between the sensory properties and fat ingredients of lipsticks (de Clermont-Gallerande et al, 2018); augmented bio-based lipids for cosmetics (Duprat-de-Paule et al, 2018); tamanu oil and skin active properties: from traditional to modern cosmetic uses (Raharivelomanana et al, 2018); lipids from seaweeds: selective extraction of potential active compounds (Terme et al, 2018); separation and identification of polar polyphenols in oily formulation using high-performance thin-layer chromatography and mass spectroscopy techniques (Fadel et al, 2018); the concept of sphingolipid rheostat in skin: a driving force for new active ingredients in cosmetic applications (Popa, 2018); oily formulations challenge: how to evaluate their beneficial effects in hydrophilic cell-based models? (Olivier et al, 2018); non invasive in vivo methods to measure lipidic formulae efficacy at the skin surface: advantages and limits (Prestat-Marquis, 2018).…”
mentioning
confidence: 99%